The protective role of Lactobacillus reuteri in a DSS-induced ulcerative colitis mouse model - Mohsen Nazari; Rezvan Goodarzi; Atefeh Yazdan Panah; Iraj Amiri; Yasser Bagheri; Babak Asghari (PLoS ONE, 2025)
Ulcerative colitis (UC) is a chronic inflammatory disease of the colon, marked by symptoms such as mucosal ulceration, diarrhea, and abdominal pain. The dextran sodium sulfate (DSS)-induced murine model replicates clinical and histological features of UC and is widely used to explore potential treatments. Lactobacillus reuteri has emerged as a promising probiotic due to its immunomodulatory and anti-inflammatory properties. This study investigates the effects of L. reuteri supplementation on histopathology, inflammatory cytokines, intestinal barrier function, and short-chain fatty acid (SCFA) production in DSS-induced colitis. Male Balb/C mice were divided into control, DSS-induced colitis, and DSS + L. reuteri treatment groups. The colitis model was established with 3% DSS in drinking water for seven days, and mice in the treatment group received 10 10 CFU of L. reuteri daily. Disease activity index (DAI), colon length, myeloperoxidase (MPO) levels, cytokine concentrations, tight junction protein expression, and SCFA production were measured to evaluate treatment effects. Histological analyses assessed inflammation, crypt damage, and ulceration. Mice treated with L. reuteri exhibited significant improvements across all evaluated parameters. Supplementation mitigated weight loss, reduced DAI, and restored colon length. MPO levels and pro-inflammatory cytokines (TNF-α, IL-1β, IL-6) were significantly reduced, while anti-inflammatory IL-10 levels were elevated. Histological scores showed decreased inflammation, crypt damage, and ulceration. L. reuteri enhanced tight junction protein expression, particularly ZO-1 and Claudin-1, and significantly increased SCFA production, improving gut barrier integrity and microbial function. L. reuteri supplementation effectively mitigates DSS-induced colitis by reducing inflammation, restoring intestinal barrier integrity, and enhancing microbial metabolism. These findings suggest L. reuteri as a promising therapeutic candidate for UC management.